Analysis of The Strategy for Developing Facilities and Infrastructure in Non-JKN Outpatient Services Using The Balance Scorecard Method at RSGM Unjani Cimahi In 2025 - Harjasa, Panji; Yoshida, Eka; Aziz , Abdul (IJBLE Scientific Publications Community Inc., 2025)
The rapid development of healthcare services requires organizations to adapt to an increasingly dynamic and competitive business environment. The Dental and Oral Hospital (RSGM) Unjani Cimahi holds a strategic position as the only specialized hospital providing dental and oral healthcare services in Cimahi City. This study aims to formulate strategies for developing facilities and infrastructure in non-JKN services. The research method used is descriptive qualitative with SWOT and Balance Scorecard analysis approaches. Data were obtained through in-depth interviews with seven informants, consisting of one Mandiri Inhealth (Identity) user, one non-JKN patient using personal/cash services, and five informants from the board of directors and related parties at RSGM Unjani Cimahi. The results of the Balance Scorecard analysis indicate that, in the learning and growth perspective, the strategic target is the realization of a healthy work culture and a reward system that enhances employees' affective commitment. In the internal process perspective, the strategic targets include improving compliance with service SOPs, achieving registration and payment waiting times in accordance with WHO and Ministry of Health standards, and optimizing the availability of executive polyclinic facilities. From the customer perspective, patient satisfaction is positioned as a key success factor through the provision of targeted executive polyclinic services that attract patient interest and contribute to hospital revenue growth. From a financial perspective, the strategic target focuses on increasing revenue through diversification of income sources and more efficient financial management aligned with productive expenditures.